The Impact of Script Type Cooperative Learning Model Implementation on Mathematics Learning Outcomes in Class VIII Junior High School Students - Chairuddin Chairuddin (JME (Journal of Mathematics Education), 2021)
This is an experimental study to determine (1) the mathematics learning outcomes of class VIII students at SMP Negeri 16 Poleang Tengah after being taught using a script type cooperative learning model on cube and block material; (2) the mathematics learning outcomes of class VIII students at SMP Negeri 16 Poleang Tengah after being taught using conventional learning models on cubes and blocks; and (3) the mathematics learning outcomes of students who are taught using a script-type cooperative learning model on cube and block material. The hypothesis of this study is that using the Script Type cooperative learning model to teach students mathematics is more effective than using traditional learning models on cube and block material in class VIII SMP Negeri 16 Poleang Tengah. The participants in this study were all students in class VIII, who were divided into three parallel classes with a total of 60 pupils. The Cluster Random Sampling approach was used to sample the two classes, one of which was designated as the control class and the other as the experimental class. A total of 40 people were included in the study from both classes. Data is retrieved through learning outcomes assessments, which are then utilized to collect information on students' math learning results. Descriptive and inferential statistics were employed in the data analysis technique. Inferential research using the t-test yielded a value of tcount = 2.293 in sig. = 0.027 = 0.05, indicating that H0 is rejected and H1 is accepted. This inferentially means that there is a significant difference in the mathematics learning outcomes of students in Class VIII SMP Negeri 16 Poleang Tengah who are taught the Script-type cooperative learning model versus the conventional learning model. Based on the findings of these research, it can be stated that using the script type cooperative learning model to teach students mathematics is more effective than using traditional learning models for class VIII students at SMP Negeri 16 Poleang Tengah.